2021
DOI: 10.1155/2021/6619149
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Nomogram for Gallbladder Cancer after Surgical Resection: A Single-Center Experience

Abstract: Background. Gallbladder cancer (GBC), which accounts for more than 80% of biliary tract malignancies, has a poor prognosis with an overall 5-year survival less than 10%. The study aimed to identify risk factors and develop a predictive model for GBC following surgical resection. Methods. 98 GBC patients who underwent surgical resection from Guangdong Provincial People’s Hospital were enrolled in the study. Cox-regression analysis was performed to identify significant prognostic factors. A nomogram was construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Therefore, resection margin positivity is a common histopathological finding in GBC since they cannot be operated curatively. The ratio of resection margin 1 patients is 36.8% and is compatible with the literature 1 , 6 , 7 , 35 . The statistically significant distinction in the short overall survival time in this group of patients underlines the need for a complete resection during the operation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, resection margin positivity is a common histopathological finding in GBC since they cannot be operated curatively. The ratio of resection margin 1 patients is 36.8% and is compatible with the literature 1 , 6 , 7 , 35 . The statistically significant distinction in the short overall survival time in this group of patients underlines the need for a complete resection during the operation.…”
Section: Discussionsupporting
confidence: 91%
“…The light of the literature shows that GBC’s prognostic characteristics have been almost the same for many years 1 , 3 , 4 , 7 , 35 . Tumor size, pT staging, lymph node metastasis, perineural invasion, histological grading, RM, and liver invasion play decisive roles in the prognosis of GBC patients 1 , 4 , 6 , 7 , 35 . The present study found that the relationship between poor tumor differentiation, advanced pT, positive resection margin, the presence of perineural invasion, lymphovascular invasion, and serosal invasion with a short OS time is in agreement with the literature 1 , 3 , 6 , 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nomograms, incorporating and illustrating important prognostic factors in a visible way, have become a superior methods to accurately predict outcomes for patients with various cancers 7 , 8 . Previously, researchers have attempted to construct nomograms to predict the prognosis of patients with GBA 9 , 10 . Some novel LN schemes, such as lymph node ratio (LNR) and log odds of positive lymph node (LODDS), showed more accurate predictive ability than AJCC N status 11 13 .…”
Section: Introductionmentioning
confidence: 99%